Implementation of the Complete Systematic Land Registration Program in Aceh, Indonesia - Tari Annisha Fhonna; Dyah Mutiarin; Herdin Arie Saputra; Ikhwan Rahmatika Latif (Otoritas : Jurnal Ilmu Pemerintahan, 2021)
The Complete Systematic Land Registration Program is an effort of the Central and Local Governments to overcome various common problems in the agrarian sector. Through the granting of the legalization of assets, it is expected that the restructuring, ownership, use, and utilization of land can be carried out to create justice in the field of land tenure and ownership. This type of research is a qualitative descriptive study using a case study approach. Interviews, observations, library studies, or documentation are data collection techniques and data processing is carried out using Nvivo 12 Plus software. The results showed that the Complete Systematic Land Registration is an effort of the Central and Local Governments to accelerate the process of providing guarantees and protection of land rights in all regions of Indonesia. Complete systematic land registration program implementation in Aceh specifically Banda Aceh City and South Aceh District in general has been running well where the issuance of certificates of land for the Banda Aceh city area of 2279 plots and South Aceh regency 1,669 Plots.